Measurement of Shooting Ability of Extracurricular Basketball Students Using The Beef Concept - Sumroti, Nuning Aisyah; Handayani, Heni Yuli; Himawan, Agus; Purwoto, Septyaningrum Putri (Universitas PGRI Palembang, 2024)
This study aims to measure the extent of the shooting ability of extracurricular basketball students using the BEEF concept at MTsN Bangkalan. What was used in this study was a quantitative research method, the population in the study was MTsN Bangkalan students, while the sample that the researchers used was 25 basketball extracurricular students. With the data collection technique used in the form of saturated sampling technique. The research instrument used is a shooting technique test with the BEEF concept, which has been validated by 2 experts (expert judgment). The results of the study are from the ability of the correct shooting technique but not entering with a percentage of 76%, the ability of the correct shooting technique but entering with a percentage of 24%, the ability of the wrong shooting technique but entering with a percentage of (0), and the ability of the wrong shooting technique but not entering with a percentage of (0). It can be seen that the ability to shoot using the BEEF concept at the junior high school / MTs level is still said that the sample lacks mastery and understanding of the BEEF concept when shooting, so that the shooting is not effective and efficient.